Long Non-coding RNA Small Nucleolar RNA Host Gene 14, a Promising Biomarker and Therapeutic Target in Malignancy - Shen, Shen; Wang, Yanfang; Zhang, Yize; Dong, Zihui; Xing, Jiyuan (Frontiers in Cell and Developmental Biology, 2021)
Small nucleolar RNA host gene 1 (SNHG14) is a long noncoding RNA found to be overexpressed in various types of cancers. Moreover, the expression level of SNHG14 was closely associated with multiple clinicopathological characteristics such as prognosis, tumor differentiation, TNM stage, and lymph node metastasis. Functionally, gain- and loss-of-function of SNHG14 revealed that overexpressed SNHG14 promoted cancer cell viability, invasion, and migration, whereas its down-regulation produced the opposite effect. Mechanistically, regulating its target gene expression by sponging distinct miRNAs might be the major mechanism underlying the oncogenic functions of SNHG14. Thus, SNHG14 might be a promising prognostic biomarker and therapeutic target for cancers. In this review, we discuss the expression profile, biological function, and molecular mechanisms of SNHG14 in cancers to provide a molecular basis for the clinical utility of SNHG14 in the future.